Do Workers Discriminate against Female Bosses? - Martin Abel (Institute of Labor Economics (IZA), 2019)
I hire 2,700 workers for a transcription job, randomly assigning the gender of their (fictitious) manager and provision of performance feedback. While praise from a manager has no effect, criticism negatively impacts workers' job satisfaction and perception of the task's importance. When female managers, rather than male, deliver this feedback, the negative effects double in magnitude. Having a critical female manager does not affect effort provision but it does lower workers' interest in working for the firm in the future. These findings hold for both female and male workers. I show that results are consistent with gendered expectations of feedback among workers. By contrast, I find no evidence for the role of either attention discrimination or implicit gender bias.
Keywords: J50; J70; 330; gender discrimination; gig economy; female leadership